(x-3)*(2*y+1)=7 (2*x+1)*(3*Y-2)=-55 giúp với ạ

Question

(x-3)*(2*y+1)=7
(2*x+1)*(3*Y-2)=-55
giúp với ạ

in progress 0
Aaliyah 1 tháng 2021-11-01T14:52:43+00:00 2 Answers 10 views 0

Answers ( )

    0
    2021-11-01T14:53:56+00:00

    Đáp án+Giải thích các bước giải:

    Ta có (x – 3)(2y + 1) = 7
    $⇒ (x – 3)(2y + 1) = 1.7 = 7.1 = -1.7 = 7.-1$
    TH1 : Khi x-3 =1 và 2y +1=7
    ⇒ x = 4 và y = 3 (t/m)
    TH2 : khi x-3 = 7 và 2y + 1 =1
    ⇒ x = 10 và y =0 (t/m)
    TH3 : khi x-3 =-1 và 2y +1=-7
    ⇒ x = 2 và y = -4 (t/m)
    TH4 : khi x-3 = -7 và 2y + 1 =-1
    ⇒ x =  -4 và y =-1 (t/m)
    Vậy (x;y) nhận các gt (4;3) ; ( 10; 0) ; ( 2; -4) ; ( -4; -1)

     

    0
    2021-11-01T14:54:01+00:00

    Đáp án:

    Mình làm hơi tắt

    Giải thích các bước giải:

     +)   (x-3)(2y+1)=7=1*7=7*1=-1*(-7)=-7*(-1)

    =>x=4;y=3

        x=10;y=0

        x=2;y=-4

        x=-4;y=-1

    Vậy…

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )